SKRINING BAKTERI ENDOFIT PERAKARAN PISANG SECARA IN VITRO SEBAGAI AGEN PENGENDALI HAYATI TERHADAP PENYAKIT LAYU BAKTERI (Ralstonia solanacearum) PADA TANAMAN PISANG - Dewi Dewi Hastuti; Andree Saylendra; Eman Saeful Rohman (Jurusan Agroekoteknologi Fakultas Pertanian Untirta, 2014)
This research aimed to find and identify isolates ofendophytic bacteria in banana plants root to suppress bacterial wilt disease in banana plants (Musa aradisiaca) This research has been carried out in the Laboratory of Agroecology Department Faculty of Agriculture, Sultan Ageng Tirtayasa Universityfrom December 2012 to April 2013.This research used a completely randomized design consisting of a single factor that endophytic bacteria consisting of 10 levels: control (without bacteria), bacterial endophyte 1, bacterial endophyte 2, bacterial endophyte 3, bacterial endophyte 4, bacterial endophyte 5, bacterial endophyte 6, bacterial endophyte 7, bacterial endophyte 8, bacterial endophyte 9. The treatment repeated 4 times. The parameter done are the percentage of inhibition, antagonism between endophytic bacteria test, test bacterial gram on endophytic bacteria, and bacterial morphology. This researchindicated,that all bacteria hada potential antagonist to inhibit Ralstonia solanacearum. Of the 60 isolates, 30 isolates showed the ability to inhibit the growth of Ralstonia solanacearum in vitro. Totally of 9 isolates were selected as candidates obtained antagonist belonging to Bacillus sp. Three isolates that had the best inhibitory ability against Ralstoniasolanacearum were BE 10-812, 10-8 BE 13, and BE 10-8 29. These three isolates were identified as Bacillus sp.